Vicarious Experience: A Neglected Source of Career Identity Among Indigenous Hospitality Graduates in Uganda - Omuudu Otengei, Samson; Changha, George; Kasekende, Francis; Mpeera Ntayi, Joseph (Journal of Hospitality & Tourism Education, 2017)
The study investigates measures of vicarious experience and examines the relationship between vicarious experience and the career identity of Ugandan hospitality graduates. Questionnaires were administered to indigenous hospitality graduates (n = 248). Phenomenological findings on the concept of vicarious experience were obtained from 10 respondents. The results showed that among indigenous hospitality graduates, vicarious experience comprises two factors: professional functional excellence and social welfare construction experiences. Both factors are significant predictors of career identity among Ugandan hospitality graduates. When hospitality graduates engage in observational learning, then their career identity is enhanced. The findings thus suggest observational learning (vicarious experience) as an alternative route to stimulating a particular form of career motivation (career identity). Therefore, hotel managers who wish to build career identity may foster an atmosphere in which vicarious experiences are appreciated and valued by all.
Keywords: Career identity; Functional experience; Hospitality graduates; Social welfare construction; Vicarious experience